1996
DOI: 10.1111/j.1476-5381.1996.tb15262.x
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of B1 receptor mediating des‐Arg9‐BK‐induced rat paw oedema by systemic treatment with bacterial endotoxin

Abstract: 1 The effect of pretreatment with bacterial endotoxin (LPS, 10 pg, i.v., 24 h) on the bradykinin B1 and B2 receptor-induced oedema in the rat paw, and the interaction of B,-mediated responses with other inflammatory mediators, was investigated. 2 Intraplantar (i.pl.) injection of the selective B1 agonist, des-Arg9-BK (DABK, 100 nmol) in naive animals pretreated with the angiotensin converting enzyme inhibitor, captopril caused a small increase in paw volume (0.04 + 0.003 ml, mean + s.e.mean, n = 6), while the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
53
2
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 43 publications
10
53
2
2
Order By: Relevance
“…Similar findings have been reported in other models in which sensitization of responses mediated by BKB 1 receptor is associated with a clear reduction of BKB 2 receptor-mediated effects (Cruwys et al, 1994;Campos et al, 1996;El Sayah et al, 2006). For instance, Campos et al (1996) have shown that LPS causes an increase in BKB 1 receptor-mediated rat paw edema, accompanied by a patent drop in the BKB 2 receptor-mediated edematogenic response. Recently, El Sayah et al (2006) have reported that BKinduced contractile responses in isolated LPS-treated pig iris sphincter muscle are markedly reduced in a time-dependent process.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Similar findings have been reported in other models in which sensitization of responses mediated by BKB 1 receptor is associated with a clear reduction of BKB 2 receptor-mediated effects (Cruwys et al, 1994;Campos et al, 1996;El Sayah et al, 2006). For instance, Campos et al (1996) have shown that LPS causes an increase in BKB 1 receptor-mediated rat paw edema, accompanied by a patent drop in the BKB 2 receptor-mediated edematogenic response. Recently, El Sayah et al (2006) have reported that BKinduced contractile responses in isolated LPS-treated pig iris sphincter muscle are markedly reduced in a time-dependent process.…”
Section: Discussionsupporting
confidence: 73%
“…This molecular phenomenon results in a marked sensitization of responses elicited by BKB 1 receptor agonists (Marceau et al, 1998). In contrast, it has been shown that BKB 2 receptor-mediated responses can be desensitized, through mechanisms not yet fully elucidated, after prolonged exposure to proinflammatory stimuli (Cruwys et al, 1994;Campos et al, 1996;El Sayah et al, 2006). Although it has been shown that BK-induced contractile responses in human umbilical artery (HUA) are mediated by BKB 2 receptor subtype activation (Feletou et al, 1995;Abbas et al, 1998), possible changes in BK-mediated effects after prolonged in vitro incubation have not been yet analyzed in this tissue.…”
mentioning
confidence: 94%
“…The B 1 type receptor has, however, attracted interest because of its apparent ❏ upregulation following some types of tissue inflammation and, consequently, the view that B 2 receptors dominate kinin pharmacology may be tempered by the fact that inflamed tissue may exhibit an enhanced response to kinins through B 1 receptor upregulation [21]. Indeed, upregulation of response to the B 1 receptor agonist des-Arg 9 -bradykinin and de novo synthesis of B 1 receptor was demonstrated after prolonged incubation of tissues in Krebs solution [22,23] and was increased by LPS [24] or IL-1β [25,26]. B 1 receptor upregulation within only 1 h is unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…Carrageenin, a waterextractable polysaccharide obtained from various seaweeds, induces macrophage accumulation in fluid exudates from subcutaneous chambers in dogs (Hou et al 2004). Carrageenin activates kinin release and induces kinin B1 receptor (Campos et al 1996;Decarie et al 1996;Ni et al 2003). Bradykinin, one of kinins, enhances vascular permeability and then causes inflammatory edema.…”
Section: Discussionmentioning
confidence: 99%